Habitação e sua relação com o direito à cidade no capitalismo contemporâneo : um estudo sobre o programa Minha Casa Minha Vida Faixa 1 em Vitória-ES - Rangel, Shanna de Oliveira (2018)
This dissertation focuses on the current debate on the right to housing in Brazil and its relationship with the right to the city, with a focus on the My Home My Life Program (Band 1) in the city of Vitória / ES. For that, a theoretical study was carried out based on thinkers who discuss the right to housing and the city, as well as the field research, aiming to answer some questions pointed out in this study, contemplating the articulation of quantitative and qualitative data. The investigative process involved the following questions: How does the My Home My Life Band 1 program in the city of Vitória / ES guarantee access to housing? The right to the city can be guaranteed from the access to the house by the program My House My Life in Vitoria - Band 1? This work sought to identify the process of constitution of housing as a social right and its unfolding in the logic of capitalist production. With regard to the general objective, the objective was to analyze the My Home My Life Band 1 housing program in the city of Vitória, in order to understand if there is a guarantee of the right to the city, based on access to housing, from the perspective of its users. The work involved documentary research and field research. In the field research the focal group was carried out and, in terms of data treatment and analysis, content analysis and thematic analysis technique were used. As the main conclusions of the study regarding the My Home My Life program - Band 1 in the city of Vitória / ES, we verified that social factors can have consequences for the non-effective housing as a constituent part of the right to the city. consequence of the logic of how space is produced, the city, the dwelling, modifying the ways of life on the influence of the capitalist mode of production.